The role of host pigments in coral photobiology - Ferreira, Gabriel; Bollati, Elena; Kühl, Michael (Frontiers in Marine Science, 2023)
Corals have the ability to synthesize various pigments, responsible for their characteristic vivid coloration. Most coral host pigments are green fluorescent protein (GFP)-like pigments exhibiting diverse spectral properties covering almost the entire visible spectrum, with pigments fluorescing from cyan to red. The type of pigment a coral will synthesize can vary inter-and intraspecifically. To this day, the precise role of fluorescent pigments in corals has not been fully elucidated. Fluorescent pigments have the ability of modifying local light fields and could thus represent an asset for the coral to optimize the light exposure of its photosymbiont. Such fine-tuning of the light microenvironment could enable the animal to adapt to broader environmental conditions by optimizing symbiont photosynthesis. This can involve energy transfer between host pigments, as well as modulation of their scattering properties via tissue plasticity and granule formation that affect the distribution and organization of fluorescent host pigments in coral tissue. These mechanisms can enable either photoprotection or photoenhancement depending on the coral's environment. In this review, we summarize and discuss current knowledge about the link between fluorescent pigments and symbiont photosynthesis in coral, and discuss limitations and challenges of experimental investigation of this connection.